2017
DOI: 10.1155/2017/6519785
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiome and Inflammation: A Study of Diabetic Inflammasome-Knockout Mice

Abstract: Aims Diabetes is a proinflammatory state, evidenced by increased pattern recognition receptors and the inflammasome (NOD-like receptor family pyrin domain (NLRP)) complex. Recent reports have elucidated the role of the gut microbiome in diabetes, but there is limited data on the gut microbiome in NLRP-KO mice and its effect on diabetes-induced inflammation. Methods Gut microbiome composition and biomarkers of inflammation (IL-18, serum amyloid A) were assessed in streptozotocin- (STZ-) induced diabetic mice on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
109
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(113 citation statements)
references
References 24 publications
2
109
0
2
Order By: Relevance
“…The microbiome, the collective genome of all the microbiota, can have a major influence on the immune system in the gastrointestinal (GI) tract and lung. Imbalances in microbiota composition (dysbiosis) have been associated with many inflammatory conditions, including inflammatory bowel disease (IBD) in the GI tract, 1–3 and chronic obstructive pulmonary disease (COPD) and asthma in the lung as well as other systemic and metabolic diseases (e.g., gout, liver disease, obesity, type II diabetes, and psychologic disorders), 4–12 and even in cardiovascular health and diseases (reviewed in Ref. 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…The microbiome, the collective genome of all the microbiota, can have a major influence on the immune system in the gastrointestinal (GI) tract and lung. Imbalances in microbiota composition (dysbiosis) have been associated with many inflammatory conditions, including inflammatory bowel disease (IBD) in the GI tract, 1–3 and chronic obstructive pulmonary disease (COPD) and asthma in the lung as well as other systemic and metabolic diseases (e.g., gout, liver disease, obesity, type II diabetes, and psychologic disorders), 4–12 and even in cardiovascular health and diseases (reviewed in Ref. 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…The pro-in ammatory viral and bacterial pathogens cause typically disruption of TJs and result in dysfunction of gut barrier due to the loss of enterocyte microvilli [35]. Previous studies have shown that the increased Bacteroidetes is associated with dysfunction of innate immune system, resulting in host present in a pro-inflammation state [36], while de ciency of Lactobacillus spp. is involved in gut in ammation and bacterial infection [37].…”
Section: Discussionmentioning
confidence: 99%
“…NLRP3-deficient mice had altered interactions between the intestinal microbiome and the host, which may influence the progression of symptoms associated with metabolic syndromes. Furthermore, low-grade intestinal lesions were present in these NLRP3-deficient mice that depended on excessive growth of Prevotellaceae and Bacteroidetes [116], and the ratio of Firmicutes to Bacteroidetes was decreased [120]. CCL5 is caused by bacterial and viral infections and recruits a variety of innate and adaptive immune cells by activating toll-like receptors on epithelial cells [121].…”
Section: Nlrp3 and The Microbiomementioning
confidence: 99%